2018
DOI: 10.1155/2018/6079595
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study on Discriminant Analysis of Syndrome Types in the Recovery Period of Stroke in Traditional Chinese Medicine

Abstract: Objective The purpose of this study is to understand the distribution of syndrome types, the data of four diagnostic information variables, and the correlative degree and diagnostic value of four diagnosis indexes and syndromes in patients with the recovery period of ischemic stroke through clinical case data. Methods This study developed a unified clinical case collection table, following the clinical research design, measurement, and evaluation methods, using Chi-Square test, logistic regression analysis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…Discriminant analysis is one of the more complex and demanding statistical methods used in many sectors, mostly in medicine, economics, chemistry, or sociology [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. So far, multidimensional statistical methods have not found a more significant application in the field of tribotechnics.…”
Section: Discussionmentioning
confidence: 99%
“…Discriminant analysis is one of the more complex and demanding statistical methods used in many sectors, mostly in medicine, economics, chemistry, or sociology [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. So far, multidimensional statistical methods have not found a more significant application in the field of tribotechnics.…”
Section: Discussionmentioning
confidence: 99%
“…Its clinical manifestations are suddenly faint, hemiplegia, sluggish speech, and tongue skew. It is characterized by acute illness and rapid change, just like the wind [ 89 ]. An updated definition of stroke is an acute episode of focal dysfunction of the brain, retina, or spinal cord lasting longer than 24 h. The traditional definition of stroke is clinical and based on the sudden onset of loss of focal neurological function due to infarction or hemorrhage in the relevant part of the brain, retina, or spinal cord [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through a large number of reports and authoritative statistical data, it is confirmed that China has become a high-level country of cerebrovascular diseases. Stroke is not only valued in China but also one of the diseases that have aroused great attention in the world [ 89 ]. Stroke is also one of the major causes of death worldwide, with about 5.5 million people dying from it every year.…”
Section: Discussionmentioning
confidence: 99%
“…Different forces are applied at key points to make the pulse in three states of floating, middle and sinking [ 3 ], and the amplitude, frequency and shape of the pulse signal are sensed, so as to discover, dig and extract the pulse condition information hidden behind the pulse signal [ 4 ]. According to the internal relationship between human health state and pulse condition, the human health state is analyzed to achieve the purpose of disease screening [ 5 , 6 , 7 ]. Although this method can quickly, safely and non-invasively realize the patient’s health detection and disease diagnosis, it is greatly affected by subjective factors and can find it difficult to accurately identify the pulse condition, which affects the analysis of human health status.…”
Section: Introductionmentioning
confidence: 99%